Japan's new national-security and defence strategies. Issue 1 (2nd January 2023) - Unknown
Abstract : Japan's release in December 2022 of three transformational strategy documents signalled its intent to adopt a new approach in the coming years to national-security and defence issues. The National Security Strategy pledges to increase defence spending from roughly 1.0% of GDP to 2.0% by the fiscal year beginning in 2027. The documents also call for Japan's armed forces to acquire counterstrike missile capabilities and launch new efforts to overcome the civil–military divide that has long undermined Japan's defence sector by hindering the development and adoption of new capabilities.